Pension Trustee's Investment Guide. - Jolly, Robin Ellison (Thorogood Pub., 2007)
Far too many pension trustees - even in large funds - have an inadequate understanding of investment and financial markets. This book - tailored specifically for pension fund trustees - fills an important knowledge gap.